2017
DOI: 10.3390/rs9040390
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration Mapping in a Heterogeneous Landscape Using Remote Sensing and Global Weather Datasets: Application to the Mara Basin, East Africa

Abstract: Actual evapotranspiration (ET) is a major water use flux in a basin water balance with crucial significance for water resources management and planning. Mapping ET with good accuracy has been the subject of ongoing research. Such mapping is even more challenging in heterogeneous and data-scarce regions. The main objective of our research is to estimate ET using daily Moderate Resolution Imaging Spectroradiometer (MODIS) land surface temperature and Global Land Data Assimilation System (GLDAS) weather datasets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…The latter mainly depends on the remotely sensed land surface temperature and the grass reference evapotranspiration (Senay et al, 2013). Alemayehu et al (2017) demonstrated that the SSEBop ET for the study area explained about 52, 63 and 81 % of the observed variability in the MODIS NDVI at 16-day, monthly and annual temporal resolution. Also, they suggested that the estimated ET can be used for hydrological model parameterization.…”
Section: The Evapotranspirationmentioning
confidence: 87%
“…The latter mainly depends on the remotely sensed land surface temperature and the grass reference evapotranspiration (Senay et al, 2013). Alemayehu et al (2017) demonstrated that the SSEBop ET for the study area explained about 52, 63 and 81 % of the observed variability in the MODIS NDVI at 16-day, monthly and annual temporal resolution. Also, they suggested that the estimated ET can be used for hydrological model parameterization.…”
Section: The Evapotranspirationmentioning
confidence: 87%
“…For example, land surface ET accounts for approximately 60% of the mean annual land precipitation in the global hydrological cycle [2]. Studies of ET in irrigated agricultural areas have reported the mean annual (actual) ET to accounts for more than 60% of the mean annual precipitation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…With a one-time calibration for bias removal, the model is capable of processing historical remote sensing data going back to 1984 (Senay et al, 2017). Similarly, Alemayehu et al (2017) demonstrated the effectiveness of the two-parameter formulation for ET mapping in the Mara Basin, a hydro-climatically complex system in East Africa.…”
Section: Resultsmentioning
confidence: 85%